ANALISIS CAPITAL ADEQUACY RATIO (CAR) DANA PIHAK KETIGA (DPK) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP PENYALURAN KREDIT PERBANKAN ( STUDI KASUS PADA PT. BPR CHRISTA JAYA PERDANA) - Damaris Aprilya Zacharias; Wehelmina M Ndoen; Christien C Foenay (Universitas Nusa Cendana, 2019)
The purpose of the research was to find out and to analyze the Capital Adequacy Ratio (CAR), Third Party Fund (DPK), and Loan to Deposit Ratio (LDR) to credit distribution, and to compare the application of the principle of credit distribution. Analysis techniques used in this research is financial theories based on basic assumptions. Based the research, the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) does not affect the credit distribution and Third Party Fund (DPK) significantly influences toward credit distribution of the bank. Analysis of the application of credit distribution from the bank to debtor, there are 2 principles that have not been implemented effectively. Keywords : Credit Distribution, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio(LDR), Third Party Fund (DPK)